Elaboração e validação de instrumento para avaliação de serviços públicos de fisioterapia em região de fronteira - Costa, Wilson Alexandre Cabral (2024)
Introduction: Assessing the quality of the health service becomes a complex challenge from a technical and organizational point of view, as it involves several actors (provider-usermanagers-professional s). However, a periodic assessment of the quality of these services is necessary, given the public resources involved. Objective: Develop and validate an instrument for evaluating the quality of public physiotherapy services located in a border region. Methods: This is a methodological study, with a quantitative approach, a literature review was carried out using Scoping Review, to identify existing assessment instruments. The proposed instrument matrix (Q-FISIOSUS) was created using a logical model of the service provided, which was validated in terms of content and appearance by nineteen judges using the Delphi technique. The content and appearance validity of the instrument were considered adequate in the second round of questions. The data were analyzed using the Content Validity Index (CVI) and Content Validity Ratio (CVR), and considered the overall agreement of the instrument items by the judges and their dimensions (structure, process and result). The level of consensus expected for this study was 75% of the CVI and 0.99 of the CVR. The classification of instrument scores was designed based on the percentile of tests with non-normal distribution. Results: The Scoping Review showed a lack of literature in identifying standardized instruments for evaluating the quality of public physiotherapy services in the professional's perception. The logical model of the matrix initially made it possible to create 29 instrument evaluation items (Q-FISIOSUS), which ended in 23 items after established agreement analyses. The experts' degree of compliance with the global instrument (CVI=80.99%; CVR=0.6) was considered acceptable. In the second round, the average IVC and CVR of the dimensions (structure, process and result) presented acceptable results (73.53% and 0.5; 85.40% and 0.7; 81.37% and 0.6, respectively). The scores and percentile classification levels for the global instrument and its dimensions were: compliant (10%), pressure (15%), insufficient (25%), non-compliant (50%). Final considerations: It is expected that the “Q-FISIOSUS” instrument, developed and validated, will be a practical tool in the evaluation of public physiotherapy services in border regions.